Thermal properties and thermoelasticity of L12 ordered Al3RE (RE = Er, Tm, Yb, Lu) phases: A first-principles study. (15th July 2016) - Pan, Rong-Kai; Wang, Hai-Chen; Shi, Tao-Tao; Tian, Xiao; Tang, Bi-Yu
Abstract: Thermal properties and thermoelasticity of L12 Al3 RE (RE = Er, Tm, Yb, Lu) phases have been studied by first principles calculations combined with density functional perturbation theory and quasi-harmonic approximation. In the temperature range considered, the calculated thermal properties including equilibrium volume, isothermal bulk modulus, Grüneisen parameters for different Al3 RE phases exhibit analogous variation tendency and the numerical values are associated with the atomic radius of RE. The calculated thermal expansion and heat capacity for different Al3 RE are almost indistinguishable from each other. The obtained elastic constants and polycrystalline elastic moduli exhibit gentle softening trends with temperature, and the variation tendency is also very similar. In the temperature range considered, Al3 RE phases are nearly isotropic. The present study would be valuable for future investigation and design of high temperature Al alloys. Graphical abstract: Highlights: The thermal properties of Al3 RE phases exhibit similar variation trends with temperature. The values of thermal properties are associated with atomic radii of RE. The thermoelasticity of Al3 RE phase exhibits gentle softening trend. The gentle softened thermoelasticity of Al3 RE originates from the thermally stable Al-RE bonding.